The Effects of Contract Mechanism Design and Risk Preferences on Biomass Supply for Ethanol Production. Issue 3 (30th January 2017) - Wamisho Hossiso, Kassu; De Laporte, Aaron; Ripplinger, David
ABSTRACT: This study used a stated choice experimental survey to evaluate the effects of contract design mechanisms and farmers' risk preferences in supplying biomass for ethanol production in a vertically coordinated biomass supply chain in Northern Plain of the United States. A rank‐ordered logit model was used to assess the effects of price‐ and quantity‐based contract mechanisms, risk preferences, and farm characteristics on ranking of contract preferences. Our empirical results show that, under price‐based contract, farmers are likely to prefer contract that set fixed price when a contract was offered over short term, however, over the long term, farmers prefer a contract item that set formula with a floor price. Under quantity‐based design mechanism, our model results illustrate that contract items that limit biomass quantity delivery requirement become less preferable even if farmers are allowed to negotiate on delivery price. In addition, farmer's risk perception factors toward engaging in marketing organization and vertically coordinated supply chains play a significant role in ranking contract preferences. [EconLit citations: D82; Q13; Q42]